The high 2D:4D finger length ratio effects on atherosclerotic plaque development - ÖZDOĞMUŞ, NECMETTİN ÖMER; VERİMLİ, URAL (ELSEVIER IRELAND LTD, 2010)
Background: The index finger to ring finger length ratio (2D:4D) of the right hand are affected by prenatal testosterone levels in male. To date, it has been determined that the high 2D: 4D ratio is related to the myocardial infarction, however no research has revealed the relationship between the high 2D: 4D ratio whose coronary artery shows atherosclerotic plaque development. Objective: The aim of this study was to display the relationship between the 2D: 4D ratio and atherosclerosis formation in male autopsy cases. Methods: We designed a study in 100 heterosexual male autopsies whose mean age was 21.4 +/- 2.47 (range between 17 and 25). The 2nd and 4th digits were measured on the palmar surface of the right hand and taken the right coronary artery to show the atherosclerotic plaque development. Results and conclusion: Grade 3 group had significantly higher 2D: 4D ratio compared to Grade 1 and Grade 2 groups (p = 0.02 for both). (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: 2D:4D; Coronary artery; Atherosclerosis; Finger; Digit; 4TH DIGIT LENGTH; 2ND; TESTOSTERONE; PREDICTOR; EXPOSURE; ESTROGEN; DEFECTS; HORMONE; DISEASE; 2D/4D